HUBUNGAN KEBIASAAN OLAHRAGA DENGAN DYSMENORRHEA PRIMER REMAJA PUTRI - Susianty, Nevi; Fitria, Sarah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Dysmenorrhea or menstrual pain is a common condition experienced by many young women during menstruation. One factor that is believed to influence the incidence of dysmenorrhea is exercise habits. The aim of this research was to determine the relationship between exercise habits and primary dysmenorrhea in female adolescents at SMAN 03 Mandau. This research is quantitative research. This research uses a correlational design using a cross-sectional study approach. The population for this research was all 480 female students in class X and XI of SMAN 03 Mandau. The sample in this study was part of the total object, namely 218 female students taken using a random sampling system. The research results show that the p value < α (p=0.003) means that there is a relationship between exercise and the incidence of primary dysmenorrhea in young women at SMA N 3 Mandau. The conclusion in this study is that exercise habits influence the incidence of primary dysmenorrhea because during early puberty the hormone gonadotropin is produced. Exercise has significant benefits in reducing the intensity of dysmenorrhea pain and improving the quality of life of adolescent girls. It is important for health workers, educators, and parents to encourage adolescent girls to participate in regular physical activity as part of strategies to manage and prevent dysmenorrhea.Keyword: Sports habits, dysmenorrhea, adolescent girls